Evaluation of Adherence to the Guideline in Diagnosis of Tuberculosis Patients Attending Yekatit 12 Hospital Medical College. 2023 - Mulugeta, Betelhem Alemu; Jeldu, Hosaena Alemayehu; Gebremariam, Samrawit Teame; Desta, Birrur Delelegn; Woldie, Biruk Getachew; Mandefro, Bethel Tadesse; Azale, Abrham Workineh; Tollosa, Tewodros Challa; Wollel, Mekdes Molla; Telila, Eden Kebede; Fentaw, Dagmawi Mulugeta; Abafita, Robel Nasser; et al. (British Journal of Healthcare and Medical Research, 2025)
Background: Tuberculosis has plagued humanity for centuries, causing significant suffering. References to the disease may even be found in the Old Testament, dating back to when the Israelites lived in Egypt, where TB was widespread. The term "tuberculosis" was first introduced by Lanneal and Bayle in the early 19th century. In 1882, Robert Koch identified the TB bacillus, marking a breakthrough in understanding the disease. Chalmette and Querin later laid the foundation for the Bacillus Calmette-Guérin (BCG) vaccine. TB chemotherapy began in 1943 with the introduction of streptomycin, followed by para-aminosalicylic acid in 1951. Short-course chemotherapy became the standard of care in the mid-1970s. Objectives: To evaluate the quality of TB diagnosis based on national tuberculosis guidelines. Methods: A retrospective study was conducted at Yekatit 12 Hospital, reviewing the records of patients of all ages treated for Tuberculosis (TB) between September 8 and October 9, 2023. Two nurses and one medical intern evaluated patient charts, sputum microscopy results, and radiographic records to assess adherence to diagnostic criteria. The collected data was checked for completeness and analyzed using SPSS software 24.1. Results: Out of the 116 patient records reviewed, 38 (32.6%) were diagnosed with smear-positive pulmonary TB (PTB), 48 (41.4%) with smear-negative PTB, and 30 (25.9%) with extrapulmonary TB (EPTB). Among those with smear-positive PTB, 24 (63.2%) were diagnosed correctly based on national guidelines. However, only 15 (31.2%) met the diagnostic criteria for smear-negative PTB cases when cases with three consecutive negative smears were excluded. Encouragingly, more than half of the patients diagnosed with lymph node TB had findings that aligned with national guidelines. Conclusion and Recommendation: Non-adherence to national TB diagnostic guidelines remains a significant challenge at Yekatit 12 Hospital. This gap in adherence underscores the need for targeted interventions to improve diagnostic practices. To enhance diagnostic accuracy and patient outcomes, it is essential to identify and implement strategies that encourage better compliance with these guidelines among clinicians. This could include regular training, closer monitoring, and more precise guidelines to ensure consistent and accurate TB diagnoses.